Extending P2PMesh: topology‐aware schemes for efficient peer‐to‐peer data sharing in wireless mesh networks. Issue 5 (25th February 2011) - Alasaad, Amr; Gopalakrishnan, Sathish; Leung, Victor C.M.
ABSTRACT: Wireless mesh networks (WMNs) have emerged as a promising technology that provides low‐cost broadband access to the Internet for fixed and mobile wireless end users. An orthogonal evolution in computer networking has been the rise of peer‐to‐peer (P2P) applications such as P2P data sharing. It is of interest to enable effective P2P data sharing in this type of networks. Conventional P2P data sharing systems are not cognizant of the underlying network topology and therefore suffer from inefficiency. We argue for dual‐layer mesh network architecture with support from wireless mesh routers for P2P applications. The main contribution of this paper is P2PMesh: a topology‐aware system that provides combined architecture and efficient schemes for enabling efficient P2P data sharing in WMNs. The P2PMesh architecture utilizes three schemes: (i) an efficient content lookup that mitigates traffic load imbalance at mesh routers; (ii) an efficient establishment of download paths; and (iii) a data transfer protocol for multi‐hop wireless networks with limited capacity. We note here that the path establishment and data transfer schemes are specific to P2P traffic and that other traffic would use routes determined by the default routing protocol in the WMN. Simulation results suggest that P2PMesh has the potential to improve the performance of P2P applications in a wireless multi‐hop setting; specifically, we focused on data sharing, but other P2P applications can also be supported by this approach. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : The main contribution of this paper is P2PMesh: a topology‐aware system that provides combined architecture and efficient schemes for enabling efficient P2P data sharing in WMNs (Figure 1). The P2PMesh architecture utilizes three schemes: (i) an efficient content lookup that mitigates traffic load imbalance; (ii) an efficient establishment of download paths; and (iii) a data transfer protocol for multi‐hop wireless networks with limited capacity.